Expressions and clinical significance of CCN5 and E-cadherin in primary and recurrent lesions of breast cancer - Zhou, Guofeng; Gui, Xingxing; Qu, Wei; Zhang, Xiujuan (Frontiers in Genetics, 2024)
Background: Breast cancer recurrence and lymph node metastasis significantly impact patient outcomes. Understanding the molecular mechanisms behind these processes is crucial for developing effective treatments. CCN5 and E-cadherin are proteins involved in cell adhesion and epithelial-mesenchymal transition (EMT), playing roles in breast cancer progression. Objective: This study aimed to analyze the expression levels and clinical significance of CCN5 and E-cadherin in primary and recurrent breast cancer lesions. Methods: Immunohistochemical staining using the SP method was performed to detect CCN5 and E-cadherin expression levels in 28 normal breast tissue samples, 52 primary breast cancer lesions, and paired recurrent chest wall lesions. The expression levels of these proteins were compared across different tissue types and correlated with lymph node metastasis. Results: CCN5 and E-cadherin expression levels significantly differed among normal breast tissues, primary breast cancer lesions, and recurrent lesions (Χ2=18.934 and Χ2=14.516, P<0.05). Primary breast cancer lesions exhibited higher CCN5 and E-cadherin expression levels compared with recurrent lesions and normal tissues, although these differences were not statistically significant. Patients without lymph node metastases exhibited significantly higher expression levels of CCN5 and E-cadherin compared with those with lymph node metastases (Χ2=9.775, Χ2=9.1479, P<0.05). A positive correlation between CCN5 and E-cadherin expression levels was found in breast cancer tissues (r=0.398, P<0.001). Conclusion: CCN5 and E-cadherin were expressed at lower levels in recurrent breast cancer tissues and those with lymph node metastases, indicating their potential roles in breast cancer recurrence and metastasis. These findings suggest that CCN5 and E-cadherin might work synergistically to influence breast cancer progression.